Crystal Structure and Hydrogen Storage Behaviors of Mg/MoS2 Composites from Ball Milling - Han, Zongying; Zhou, Shixue; Wang, Naifei; Zhang, Qianqian; Zhang, Tonghuan; Ran, Weixian (Journal of Wuhan University of Technology. Materials science edition, 2016)
The Mg/MoS2 composites were prepared by ball milling under argon atmosphere,and the effect of MoS2 on the crystal structure and hydrogen storage properties of Mg was investigated.It is found that 10 wt% of MoS2 is sufficient to prevent particle aggregation and cold welding during the milling process.The crystallite size of Mg will remain constant at slightly less than 38.8 nm with the milling process due to the size confinement effect of MoS2.The dehydrogenation temperature of MgH2 is reduced to 390.4-429.4 ℃ due to the crystallite size reduction.Through fitting by Johnson-Mehl-Avrami model,it is found that Mg crystal grows by three dimension controlled by interface transformation during the process of MgH2 decomposition.MoS2 has a weak catalyst effect on the decomposition of MgH2 and activation energy of 148.9 k J/mol is needed for the dehydrogenation process calculated by the Arrhenius equation.